2004
DOI: 10.1136/gut.2003.028506
|View full text |Cite
|
Sign up to set email alerts
|

Increased antigen and bacterial uptake in follicle associated epithelium induced by chronic psychological stress in rats

Abstract: Background: Chronic stress affects the course of inflammatory bowel disease and experimental colitis, and may also initiate intestinal inflammation in rats. Aim: To investigate the effects of stress on the M cell containing follicle associated epithelium, specialised in antigen uptake. Subjects and methods: Wistar rats were submitted to acute water avoidance stress for one hour or chronic water avoidance stress for 1 hour/day for 10 consecutive days. Permeability to 51 Cr-EDTA, horseradish peroxidase, and chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
94
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(103 citation statements)
references
References 38 publications
8
94
0
1
Order By: Relevance
“…In the FAE we found a high transmucosal flux of the protein antigen, HRP, whereas 51 Cr-EDTA flux and conductance did not significantly differ between VE and FAE. These findings are in line with our previous studies in rat FAE, 8 and point to an enhanced uptake of antigens in the human FAE compared with VE, but equal paracellular permeability. Analogous to the enhanced antigen uptake, a notably higher transmucosal passage of both chemically killed K-12 and live HB101 E. coli was found, which further implies that the human FAE is prone to uptake and transport of antigens and bacteria.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In the FAE we found a high transmucosal flux of the protein antigen, HRP, whereas 51 Cr-EDTA flux and conductance did not significantly differ between VE and FAE. These findings are in line with our previous studies in rat FAE, 8 and point to an enhanced uptake of antigens in the human FAE compared with VE, but equal paracellular permeability. Analogous to the enhanced antigen uptake, a notably higher transmucosal passage of both chemically killed K-12 and live HB101 E. coli was found, which further implies that the human FAE is prone to uptake and transport of antigens and bacteria.…”
Section: Discussionsupporting
confidence: 93%
“…8 In brief, serosal samples were diluted and transferred to microtitre plates. QuantaBlut Working Solution was added and plates were incubated at 300 r.p.m.…”
Section: Hrp Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…[48][49][50][51][52][53][54] Additionally, stress can change the function of mucosalassociated immune cells and cause increased antigenic and bacterial uptake. 55,56 Multiple studies have been published that have shown that the composition of gut microbiota is changed in the face of acute or chronic stress, and this in turn can subsequently change the function of intestinal barrier as explained above. [57][58][59][60] There is limited data regarding the changes in intestinal barrier or GI physiology and the underlying mechanisms of it in neuropsychiatric disorders.…”
Section: Effect Of Gut Microbiota On Intestinal Permeabilitymentioning
confidence: 99%
“…The SAMP1/Yit mouse strain develops spontaneous ileal inflammation (Matsumoto et al, 1998). In this model, as well as in a water avoidance stress-induced rat model, early inflammatory lesions were observed in the FAE (Kosiewicz et al, 2001;Velin et al, 2004). Very recently, the FAE and M cells were shown to be targeted specifically by adhesiveinvasive E. coli bacteria associated with Crohn's disease (Chassaing et al, 2011).…”
Section: Cells and Gastro-intestinal Inflammationmentioning
confidence: 90%